PENGARUH SOSIALISASI PERPAJAKAN, KESADARAN WAJIB PAJAK, PEMAHAMAN PERPAJAKAN, DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PELAKU E- COMMERCE (Studi kasus pada Pelaku Usaha UMKM yang Menggunakan Layanan Berbasis E-commerce di Kabupaten Jepara) - Hidayat, Kira Ninda Sarasati; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
This study aims to determine the effect of tax socialization, taxpayer awareness, understanding of taxation, and tax rates on the compliance of e- commerce taxpayers.This study used primary data that distributed all questionnaires online through a google form obtained by a sample of 31 respondents using the voluntary sampling method. The population in this study is MSME taxpayers, business actors who use e-commerce services. The data obtained were analyzed using multiple regression analysis using the SPSS 23 analysis program.The results of this study show that tax socialization has a positive and significant effect on taxpayer compliance. Meanwhile, taxpayer awareness, understanding of taxation, and tax rates have a positive and insignificant effect on taxpayer compliance.